The Assessment of Thiol Status in Children with Neurogenic Bladder Caused by Meningomyelocele - Korzeniecka-Kozerska, Agata; Zawada, Bo?ena Okurowska; Zawada, Bo?ena Okurowska; Skutnik, Joanna Michaluk; Skutnik, Joanna Michaluk; Wasilewska, Anna; Wasilewska, Anna (Urology Journal, 2014)
<!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Purpose: Oxidative stress can cause tissue damage in many diseases. Oxidative status depends on the balance between total oxygen radical absorbance capacity and antioxidants. Neurogenic bladder (NB) is a special state where oxidative status can influence urinary tract function. We decided to measure antioxidant (thiol) status in patients with NB and assess the effect of NB on the urinary antioxidant status and to correlate it with urodynamic findings. Materials and Methods: The investigation was conducted on two groups. The first group, constituted of 41 children with NB. The second group, consisted of 20 healthy children with no abnormality in urinary and nervous systems. The antioxidant status was assessed based on the enzyme-linked immunosorbent assay of thiols. Results: The median value of urinary protein thiol level was significantly lower in NB patients than in reference group [median 48 (0.0-633.33) and 221.55 (0.17-1293] μmoL/g protein, respectively (P < .01). We found out the statistically significant differences in urinary thiol level between patients with and without overactivity (P = .017) and between catheterized and noncatheterized patients (P = .048). Conclusion: This study demonstrates that antioxidant status in patients with NB decreased and the level of thiol status depends on the grade of bladder overactivity. Oxidative stress may be involved in the pathophysiology of bladder dysfunction related to neurogenic damage. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:Standardowy; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->